Behaviour of steel and composite beam-column joints under extreme loading conditions - Chen, Kang (2018)
Historical collapse incidents of buildings under extreme loadings have attracted academic and engineering interest to conduct research studies on the resistance of beam-column joints to mobilise alternate load path and develop catenary action, in order to bridge over lost structural members. The integrity of beam-column joints greatly influences the capability of structures to develop catenary action. Up to date, experimental tests have been conducted for various types of beam-column joints subjected to column removal scenarios, which are widely used as a threatindependent approach to represent structural damages caused by extreme loadings. However, experimental programmes on composite joints with fin plate (also referred to as shear tab) and welded unreinforced flange bolted web connections are very limited, although these two types of joints are quite common in industrial practice. In the current study, experimental tests on steel and composite beam-column joints were conducted. Two types of connections, viz. fin plate and welded unreinforced flange bolted web connections were investigated under both quasi-static and impact loading scenarios. The load-resisting mechanism, failure mode, energy absorption and development of strain were presented based on test results. Tying and flexural resistances, as well as rotation capacities, were compared with design values. A comparison of quasi-static and impact tests was also conducted to quantify the contribution of strain rate effect. Furthermore, two connections, viz. fin plate connection with slotted holes and reduced beam section connection were conducted for comparison purposes. It was found that they contributed to better tying resistance and rotation capacity in comparison with conventional connections. In addition, numerical analyses on steel beam-column joints under impact loading scenarios were conducted. Three-dimensional finite element models in commercial software LSDYNA were established and validated by test results with reasonably good accuracy. The models were used to compare two proposed evaluation indices by the author, namely, energy absorption ratio and deformation ratio for steel joints subjected to impact loads. Based on test results, a component-based modelling approach for beam-column joints with fin plate and welded unreinforced flange bolted web connections was proposed. The arrangement of nonlinear springs representing steel components was adopted from Eurocode and was combined with composite slab components. Furthermore, nonlinear spring properties were defined on the basis of component test results and design codes. The proposed models were able to simulate the behaviour of beam-column joints subjected to quasi-static and impact loads with adequate accuracy. Composite slab effect and strain rate were also considered by the proposed modelling approach. In general, the current design calculation method was found to overestimate the tying resistance of both types of composite joints, especially when thicker slabs or fewer shear studs were used. The overestimation is less evident for WUF-B joints compared to FP joints. The novel FP joint was able to develop the design values of tying resistance in the test. The design values of flexural resistance and rotation capacity could be achieved by the test, especially when the beneficial effect of intermediate strain-rate was included. The aforementioned issues of the design method could be solved by using the proposed modelling approach, which could be used in design practice for engineers.